2008
DOI: 10.1021/jo8018895
|View full text |Cite
|
Sign up to set email alerts
|

Remarkably Efficient Synthesis of 2H-Indazole 1-Oxides and 2H-Indazoles via Tandem Carbon−Carbon Followed by Nitrogen−Nitrogen Bond Formation

Abstract: Synthesis of Indazoles Base-catalyzed tandem carbon–carbon followed by nitrogen–nitrogen bond formations quantitatively converted N-alkyl-2-nitro-N-(2-oxo-2-aryl-ethyl)-benzenesulfonamides to 2H-indazoles 1-oxides under mild conditions. Triphenylphosphine or mesyl chloride/triethylamine-mediated deoxygenation afforded 2H-indazoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
81
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(81 citation statements)
references
References 64 publications
0
81
0
Order By: Relevance
“…The reaction was carried out in DMF in the presence of a tertiary base 1. All four 2-nosyl derivatives yielded the expected products 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction was carried out in DMF in the presence of a tertiary base 1. All four 2-nosyl derivatives yielded the expected products 3 .…”
Section: Resultsmentioning
confidence: 99%
“…We eliminated compounds having the same substituent on both aromatic rings (e.g., compound 7(2,6) was not made). At the polymer-supported indazoles 6-oxide 18 stage, the resins were split and one half was deoxygenated using methanesulfonyl chloride in the presence of TEA1 to provide parent heterocycles 8 after cleavage from the resin. The rate of deoxygenation was substitution-dependent; target compounds without substitution on the indazole (R 1 = H) were quantitatively deoxygenated after overnight treatment, with the exception of the R 2 = CN derivative.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Base-mediated C-arylation and exploitation of this carbon−carbon bond formation for the synthesis of 2H-indazole-1-oxides via C-aryl intermediates have already been reported. 25 We analyzed all crude reaction products by LC/MS and found that the derivatives with strongly electron-withdrawing CF 3 groups underwent partial C-arylation; in addition to the main products 4, the C-aryl derivatives 10 and indazole oxide 11 were also present. As a result of the presence of the C-arylated compound, after reduction of the nitro group, C-aryl 10 was converted to the indole derivative 12.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[2] Resin-bound N,N-disubstituted Nos amides are an intriguing class of acyclic intermediates that can be converted to diverse nitrogen heterocycles.T he critical feature of these advanced intermediates is an acidic proton on the alphac arbon of the N-alkyl group due to the presence of an electron-withdrawing substituent, R 2 (Scheme 1). Exposure to ab ase, typically DBU,t riggers C-arylation [6,19,20] via at ype of Smiles rearrangement [21] involving the spiro-Meisenheimer intermediate 2.T hese C-aryl derivatives 3 have been usedt op repare various nitrogen heterocycles,i ncluding indazoles and their N-oxides, [19,22] quinazolines, [23] indoles [24] andindolin-2-ones. [25] Interestingly, N,N-disubstituted-2-nitrobenzenesulfonamides prepared from the polymer-supported aamino acid secondary amides 4 undergo another type of Smiles rearrangement, leading to N-aryl derivatives 7.…”
mentioning
confidence: 99%